Peranan Pendidikan Agama Kristen Dalam Menghadapi Masalah Pada Masyarakat Majemuk Masa Kini - Tianggur Medi Napitupulu (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
The diversity that exists in our country is something we need to thank Allah for because He is the one who created it. Everything that God has given is beautiful. Considering that Indonesia is a country that stretches from Sabang to Merauke, its diversity consists of race, ethnicity, culture and religion. Because of this diversity, we often encounter problems because we do not accept the existence of other tribes and religions around us. Allah fails us to be able to love each other and accept the existence of other people around us. The method used in this paper is the literature study method. The library study method is a method of searching for information from various sources that match the title of the journal being written, whether through books, journals, magazines, and also other relevant sources. Quoting information from various sources is carried out without comparing the opinions of each expert.